Explicit difference schemes for a pseudoparabolic equation with an integral condition - Jachimavičienė, Justina (Lietuvos matematikos rinkinys, 2012)
The aim of this paper is to analyze three layer explicit schemes for a pseudoparabolic equation with different boundary conditions, including nonlocal ones. The numerical results are presented.
Keywords: pseudoparabolic equation; three layer explicit scheme; eigenvalue problem